Investigation on sub nano-crystalline silicon thin films grown using pulsed PECVD process. (15th June 2018) - Sharma, Mansi; Chaudhary, Deepika; Sudhakar, S.; Jadkar, Sandesh; Kumar, Sushil
Abstract: Present work discusses the structural modifications in intrinsic layer of hydrogenated amorphous silicon (a-Si:H) deposited using Pulsed Wave Plasma Enhanced Chemical Vapor Deposition (PW-PECVD) technique which highlights the crystallite formation within the boundaries of nano crystallite silicon thin films. These investigations were carried out for the films deposited under the variation of applied pulsed power from 10 W to 60 W. The resultant film phases were generalized as sub-nano crystalline silicon phases. The evolution of such phases has been effectively probed using various spectroscopic and structural characterization techniques including Raman spectroscopy, Fourier Transform Infrared spectroscopy (FTIR), and Field Emission Scanning Electron Microscopy (FESEM). The observed sub-nano crystalline volume fraction varies from ~ 28–46%. This marks the modification in crystallite growth from the partial nucleation to coalescence phase. From this the importance of pulsed wave PECVD (PW-PECVD) has been discussed in terms of high growth rates as well as the extended transition zones with the formation of sub-nano crystallite structures. The study found to be specific for understanding the sub-nano crystalline phases in the film silicon having high photo-stability and photo-response like in µc/nc-Si:H (micro/nano crystalline silicon) and a-Si:H respectively.